2015
DOI: 10.1515/aupcsm-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Further investigations on a question of Zhang and Lü

Abstract: Abstract. In the paper based on the question of Zhang and Lü [15], we present one theorem which will improve and extend results of Banerjee-Majumder [2] and a recent result of Li-Huang [9].

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In [1, Example 1.13], Banerjee-Chakraborty ( [1]) have shown that f n can't be replaced by an arbitrary polynomial P [f ] = a 0 f n + a 1 f n−1 + . .…”
Section: Definition 12 ([12])mentioning
confidence: 99%
See 2 more Smart Citations
“…In [1, Example 1.13], Banerjee-Chakraborty ( [1]) have shown that f n can't be replaced by an arbitrary polynomial P [f ] = a 0 f n + a 1 f n−1 + . .…”
Section: Definition 12 ([12])mentioning
confidence: 99%
“…Observing Example 1.13 in [1] we note that f (z) = e z , P (f ) = f 2 + 2f and M [f ] = f (3) . So P + 1 = (M + 1) 2 .…”
Section: Definition 12 ([12])mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many results have been published concerning the above conjecture, (see, [2,3,4,5,6,8,10,11,16,17,18]). Next we recall the following definitions: (i) N (r, a; f |≥ p) (resp.…”
Section: Introductionmentioning
confidence: 99%
“…[3] If F and G share(1, l), then N L (r, 1; F ) ≤ 1 (r, ∞; F ) + 1 (r, 0; F ) + S(r, F ) when l ≥ 1, and N L (r, 1; F ) ≤ N (r, ∞; F ) + N (r, 0; F ) + S(r, F ) when l = 0.Lemma 2.12 [3]. Let F and G share (1, l) and H ≡ 0.…”
mentioning
confidence: 99%